PENGELOLAAN HUTAN DESA DI KPH WILAYAH VIII SEMENDO DARI PERSPEKTIF KINERJA KELEMBAGAAN - Fito Apriandana; Rahmat Safe'i; Indra Gumay Febryano; Hari Kaskoyo (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2021)
Muara Danau Village Forest Management Institution (LPHD) is a forum on forest management activities that aim to improve community welfare. At present, the condition of the farming business is not effective, so it requires some rules as a measure of success. This study aims to analyze the institution of the Muara Danau Village Forest Management Institution (LPHD) in the implementation of Village Forest Management. The research was conducted in Muara Danau Village, Semende Darat Laut Subdistrict, Muara Enim Regency, South Sumatra Province, from March to April 2020. Data were analyzed by using the SSBP approach. The results of the study showed the situation of farmers utilizing forest resources in the form of water sources and non-timber forest products. Smallholders manage the forest based on institutional structure stated in the AD/ART, and administrative sanctions. In terms of planting patterns in the arable land, the structure controls farmer behavior by using an agroforestry system. This makes Muara Danau Village Forest Management Institution (LPHD) obtain a good performance in the aspect of institutional management which is measured by the involvement of members and institutional administrators in group activities/training (91%) and the types of binding group rules in the form of written rules (AD/ART) as well as unwritten rules (84%) in managing areas measured based on the type of forest resource conservation activity (95%). However, managing businesses have not obtained optimal results, as measured by the absence of institutions that handle the marketing of forest products for groups (cooperatives). Based on the results of the research, the institution of Muara Danau Village Forest Management Institution (LPHD) is categorized as good.